Un nouveau dieu provincial chez les Viromanduens : Apollon Vatumarus - Jean-Sébastien Cocu; Stéphane Dubois; Aurélie Rousseau; William Van Andringa (Gallia)
The recent excavation of a site at Nesle and Mesnil-Saint-Nicaise, in the eastern part of the Somme district has allowed to identify the remains of a cult place installed in a valley in the beginning of the Roman Empire. Firstly centred on a cremation platform, the sanctuary received a temple with a peripheral gallery. The two shafts built beside the temple have revealed architectural blocks and and some material involved in the life of the sanctuary, among them, an inscribed mortar with a dedication to the god Apollo Vatumarus, object of this study.